The Acute Effects of Foam Rolling on Fatigue-Related Impairments of Muscular Performance - Edward Jo; Gabriela A. Juache; Desiree E. Saralegui; Douglas Weng; Shayan Falatoonzadeh (MDPI AG, 2018)
The purpose of this study was to examine the effects of self-myofascial release (MFR) via foam rolling immediately following strenuous activity on acute fatigue-related impairments of muscular performance. Healthy male (n = 16) and female (n = 9) subjects visited the laboratory three separate times. During visit 1, subjects were familiarized with performance testing procedures and the foam rolling and fatigue protocols. For visits 2 and 3, subjects were (T1) assessed for vertical jump height, velocity, and power and dynamic reaction time (DRT). Subjects then performed the exercise fatigue protocol, followed by either a foam rolling treatment (MFR) or seated rest (CON). Immediately after, subjects repeated the performance tests (T2). CON resulted in a greater percent decline from T1-T2 for average power (p = 0.03), average velocity (p = 0.02), and peak power (p = 0.03) than the MFR treatment. No between-treatment differences were detected for %∆ vertical jump height (p = 0.14) or DRT (p = 0.20). According to magnitude-based inference analysis, MFR is likely beneficial in attenuating fatigue-induced kinematic decrements (i.e., power and velocity). Based on magnitude-based inference analysis, MFR is "possibly beneficial" with respect to mitigating acute fatigue-related impairment of jump height and dynamic reaction time. Results demonstrate the plausible short-term benefits of foam rolling on muscular performance decrements associated with acute muscular fatigue from exercise.